LEGAL FRAMEWORK ANALYSIS AND THE ICA-EU PARTNERSHIP: AN UPDATE ON ENSURING A LEVEL PLAYING FIELD FOR PEOPLE-CENTRED ORGANISATIONS - Emerson, John; Moxom, Jeffrey (International Journal of Cooperative Law, 2025)
This paper builds on existing research conducted within the ICA-EU Partnership’s Legal Framework Analysis Research, which analyses the national cooperative legal frameworks of a variety of countries worldwide. The research aims to provide harmonised information on cooperative law and its provisions, bothat the national and supranational level, including a critical analysis of laws that impede or promote cooperatives, and thedegree to which the legislation can be considered adequate for cooperative development.2With greater knowledge and access to a country-based legal frameworkanalysis partly established through an open access online platform, ICA members can advance theiradvocacy and recommendations on the creation or improvement of legal frameworks andmonitor their evolution.3This paper outlines theexploratory findings and insightsgained through this current implementation with a view to analysing, based on the current work completed, the emergent trends in a discussion on the necessary elements of a strong cooperative law.